HISTORY OF ISLAMIC CIVILIZATION DURING THE REFORM PERIOD: Socio-cultural conditions, callenge, figures, government system, dakwah strategy - Ikhsaniatun Kamila; Hisyam Abdullah Omar; Nasikhin; Fihris (CV. Ulil Albab Corp, 2023)
This study aims to examine or study the role of the development of Indonesian Islamic civilization during the reformation period. This research is a library research that is qualitative in nature. Library research is research conducted by collecting library data, reading, recording and processing research materials related to the issues discussed. Learning history at the beginning of independence aims to instill a spirit of nationalism, bearing in mind that at this time, Indonesia still had to struggle to maintain its independence. Islam in Indonesia has existed since the 7th century and became more widespread in the 13th century. The success of the spread of Islam in Indonesia is among the most dynamic by cultivating religious and political da'wah. Since the era of independence, Islam has developed rapidly. This study aims to examine the existence of Islam in Indonesia today, with an overview before the reform era and after the reform era. The Islamic movement can be said to be very influential. This can be seen from the cancellation of Islamic organizations and parties. Despite its dominant influence as a result, Islam did not become the official ideology of the Indonesian nation state after independence, as in the Jakarta Charter incident, Islamic figures preferred Pancasila as the principle of a pluralistic state. Based on the results of written research that reform is defined as standing as ishlah, which in the ushul fiqh rule